2019
DOI: 10.31557/apjcp.2019.20.7.2125
|View full text |Cite
|
Sign up to set email alerts
|

Tissue P16 is Associated with Smoking Status among Indonesian Nasopharyngeal Carcinoma Subjects

Abstract: Background: Nasopharyngeal carcinoma (NPC) is a malignancy with high incidence in Southern China and South-East Asia. NPC incidence among males in Indonesia is estimated around 8.3/100,000 populations. Tobacco smoking is a common risk factor for cancer, including NPC. P16 is one of the key proteins related to the activation of apoptotic pathways, that commonly change during carcinogenesis. Carcinogenesis is often related to environmental exposure, including tobacco smoke. Objective: To analyze the association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…The histological findings of our study resembles that of endemic areas worldwide, with a predominance of NK NPC, especially that of undifferentiated type which accounts for 85.9%. The findings in the present study can be paralleled with a study conducted in North Africa, an endemic region, where almost all (92%) cases were undifferentiated carcinomas (UCNT) and in Indonesia which is estimated to have an intermediate incidence of NPC, is also characterized with majority of NK NPC type [ 22 ].…”
Section: Discussionsupporting
confidence: 83%
“…The histological findings of our study resembles that of endemic areas worldwide, with a predominance of NK NPC, especially that of undifferentiated type which accounts for 85.9%. The findings in the present study can be paralleled with a study conducted in North Africa, an endemic region, where almost all (92%) cases were undifferentiated carcinomas (UCNT) and in Indonesia which is estimated to have an intermediate incidence of NPC, is also characterized with majority of NK NPC type [ 22 ].…”
Section: Discussionsupporting
confidence: 83%
“…Previous reports have described the occurrence of p53 mutations and CDKN2A ( p16 ) deletions in ATLL [ 28 , 29 , 30 , 31 , 32 ]. Inactivation of p16 has been found in nearly 50% of all human cancers, caused by deletion, methylation, or gene mutations, leading to alterations in protein production [ 14 ]. Since the frequency of p16 deletion is reported to increase as the ATLL stage progresses [ 28 ], we expected that patients with ATLL might have lower scores for p16 expression in our immunostaining analyses compared to those with PTCL-NOS.…”
Section: Discussionmentioning
confidence: 99%
“…The human CDKN2A gene encodes a tumor suppressor protein known as p16. This cyclin-dependent kinase inhibitor regulates the G1 phase of the cell cycle and it is frequently inactivated in cancer [ 14 ]. In contrast, SOX4 is frequently overexpressed in a variety of solid tumors, where it functions as an oncogene [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study conducted in Ishikawa, Japan, the endometrial adenocarcinoma cells of the participants were treated with components of tobacco [ 23 ]. An association was found between TSU and the downregulation of the P16 tumor suppressor protein encoded by the CDKN2A gene that slows down cell division [ 24 ]. In addition, a reduction in expression was found to occur in the pathways of the cyclin-dependent kinase inhibitors P21 and P27, with their expression increasing inside the levels of transmission of the cyclins D1 and E. Moreover, previous studies have demonstrated the significant association between TSU and mutations in P53, which cause squamous cell carcinoma in the lungs.…”
Section: Introductionmentioning
confidence: 99%